STRATEGIES FOR RETENTION GLOBAL LEADERSHIP OF SMALL HIGH-TECH COMPANIES IN NARROWLY FOCUSED MARKETS - F. A. Kurakov (Ekonomika Nauki)
In the absence of the development of exports of high-tech industries, the implementation of strategic tasks for the accelerated growth of the economy set by the Decree of the President of the Russian Federation “On national goals and strategic objectives of the development of the Russian Federation until 2024” of May 7, 2018 No. 240 is unlikely. According to most researchers, the main potentially possible commodity items in non-raw materials exports, which are in demand in the world markets, are the products of engineering, pharmaceutical industry, apparatus and devices used in medicine. Therefore, the right to participate in foreign economic activity is delegated, first of all, to large domestic companies. However, today Russia is a country with a large assortment of production of simple products, which requires building a systematic approach in the formation of both economic policy in general and export in particular in the direction of developing of non-resource industries that produce high-tech products. The analysis of the strategies for retaining the leading positions in narrow niche segments in the global market, analysis of the competitive and diversifying strategy of the German company Poly-clip System, which is the world’s leading producer of clipping systems and the world leader in the food packaging segment was performed.